2020
DOI: 10.1101/2020.05.23.20093484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fevers Are Rarer in the Morning—Could We Be Missing Infectious Disease Cases by Screening for Fever Then?

Abstract: Body temperatures are less likely to reach the fever range in the morning, but it is unknown how this affects practice during disease outbreaks. We retrospectively investigated fever-range temperatures (≥100.4°F, ≥38.0°C) during seasonal influenza outbreaks and the 2009 H1N1 (swine flu) pandemic, which have recently been used as preparatory models for coronavirus disease 2019 (COVID-19). Our analyses included a nationally representative sample of records from adult visits to US emergency departments (n=202,181… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For example, different studies have shown that core body temperature in the morning maybe 0.3–0.9 °C lower than in the afternoon [ 13 , 14 , 65 ]. We did not consider circadian rhythm in our analysis, yet additional study of this variable and the need for methods to mitigate its impact in infectious disease screening is warranted [ 66 ]. In the future, we intend to provide additional retrospective analysis of our data to assess this potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, different studies have shown that core body temperature in the morning maybe 0.3–0.9 °C lower than in the afternoon [ 13 , 14 , 65 ]. We did not consider circadian rhythm in our analysis, yet additional study of this variable and the need for methods to mitigate its impact in infectious disease screening is warranted [ 66 ]. In the future, we intend to provide additional retrospective analysis of our data to assess this potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%